2008
DOI: 10.1152/jn.01020.2007
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Binary Taste Mixtures in the Nucleus of the Solitary Tract: Neural Coding With Firing Rate

Abstract: The contribution of gustation to the perception of food requires an understanding of how neurons represent mixtures of taste qualities. In the periphery, separate groups of fibers, labeled by the stimulus that evokes the best (largest) response, appear to respond to each component of a mixture. In the brain, identification of analogous groups of neurons is hampered by trial-to-trial variability in response magnitude. In addition, convergence of different fiber types onto central neurons may complicate the clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…1, 4, and 5), are not atypical for medullary neurons. Other studies of NTS units in mice and rats have shown latencies to response, and to maximal activation, to room temperature sucrose of near 1 s from stimulus onset (Chen and Di Lorenzo 2008;McCaughey 2007). Considering the present effects of cooling on latency, these lags would be expected to further increase with reduction in solution temperature.…”
Section: Considerations and Conclusionmentioning
confidence: 81%
“…1, 4, and 5), are not atypical for medullary neurons. Other studies of NTS units in mice and rats have shown latencies to response, and to maximal activation, to room temperature sucrose of near 1 s from stimulus onset (Chen and Di Lorenzo 2008;McCaughey 2007). Considering the present effects of cooling on latency, these lags would be expected to further increase with reduction in solution temperature.…”
Section: Considerations and Conclusionmentioning
confidence: 81%
“…Spontaneous firing rate was 1.9 ± 0.3 spikes per sec (sps). These cells were a subset of a dataset whose detailed tuning characteristics are described in another paper (Chen and Di Lorenzo, 2008). Cells in the present paper were those that had a sufficient number of stimulus presentations of all 10 tastants for temporal coding analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Presentation of mixtures of tastants of different qualities only adds to the confusion. We have shown that the across neuron pattern (ANP) of responses can go a long way toward resolving these ambiguities by providing a reasonable representation of the taste world (Chen and Di Lorenzo, 2008). Because the ANP is based on taste-evoked spike counts, it relies on the contribution of narrowly tuned cells; more broadly tuned cells in this model only add noise to the message.…”
Section: Introductionmentioning
confidence: 99%
“…5). Peripheral taste neurons, like rat brainstem taste neurons (Chen and Di Lorenzo, 2008), may naturally respond to multi-quality aversive stimuli. Rodents are assisted in discriminating among aversive chemosensory stimuli by sensations derived from trigeminal sensory nerves (Wang et al ., 1993; Pittman and Contreras, 1998); and, reflex salivation, elicited by sour tasting acids (Matsuo and Yamamoto, 1989; Bradley et al ., 2005), may contribute additional taste and texture cues to amplify or modify ongoing acid-elicited CT responses.…”
Section: Best-stimulus–behavior Consonancementioning
confidence: 99%